Cotton nitrogen doses in the edaphoclimatical conditions of northeastern Brazil - da Silva, Célia Maria; Ribeiro, Aureliano de Albuquerque; da Silva, Evandro Fabio; da Silva, Mayana Garcias; Alencar, Suelem Vieira; Paulo, Sebastião Andrey Vicente (Revista Brasileira de Engenharia de Biossistemas, 2023)
The study of cotton plant responses to nitrogen fertilization in different climate and soil conditions is essential for the correct management of nitrogen in this crop. Therefore, the objective of the present study was to evaluate the responses of cotton plants to nitrogen fertilization in the edaphoclimatic conditions of the Cariri region, located in the northeastern State of Ceará, Brazil. The experiment was conducted in an experimental area at the CENTEC (Centre for Technological Education) School of Technology (FATEC - Cariri campus), located in the city of Juazeiro do Norte, Ceará State. The statistical design adopted was Completely Randomized Design (CRD). The treatments were composed from the combination of four doses of nitrogen (0, 60, 120, and 180 kg ha-1 of N, equivalent to 0, 50, 100, and 150% of the N recommendation for the crop) with four replications. Urea was used as a nitrogen source. At 42 days after sowing, the plants were collected. Plant height, number of leaves, stem diameter, leaf area, absolute growth rate, shoot and root dry matter, total and nitrogen use efficiency were evaluated. The different doses of nitrogen significantly influenced all the analysed variables. In general, nitrogen doses greater than 120 kg ha-1 of N were shown to impair the growth and dry matter production of the cotton plant in the climate and soil conditions of the Cariri region, northeastern Brazil. In addition, excessive nitrogen fertilization was shown to reduce the efficiency of nitrogen use by the cotton crop.